Euroscepticism, Europhobia and Eurocriticism The Radical Parties of the Right and Left vis-Ã -vis" the European Union" - Rodriguez-Aguilera de Prat, Cesareo (Peter Lang International Academic Publishers, 2013)
This book analyses in detail the electoral manifestos and programmes presented by twenty-two parties during the European Parliamentary elections in 2009. The research indicates that radical right-wing parties usually have Europhobic impulses, however, radical left-wing parties are, in theory, favourable to European integration, but dispute the direction currently imposed by the EU authorities.
Description based on print version record.
KU Select 2018: HSS Backlist Books
Keywords: Political Science; Political science; Electronic books